Does Social Media use Impact Small Agribusiness Exploitation and Exploration Capability? Perspectives and Recommendations from the UT of J&K - Bakshi, Avantika; Chauhan, Vinay (Indian Journal of Marketing, 2022)
For businesses functioning in complex environments where destabilizing factors are exacerbated, ambidexterity, or the ability of an organization to exploit and explore, becomes essential. Due to this, businesses are on the lookout for newer procedures that are practical both now and in the future. The utilization of digital and social media for marketing forms a subset of such practices that are contemporary yet pervasive. In fact, Whatsapp and Facebook have become the spearhead platforms for information dissemination, relationship building, and transaction handling for businesses around the globe. While considerable research provides insights into the adoption and acceptance of web technologies in different sectors, studies investigating the role of social media in developing dynamic capabilities for agribusinesses are scarce. Data inputs were drawn from 73 agribusinesses primarily using a quantitative approach and interpreted using partial least squares structural equation modeling (PLS-SEM) to address this issue. A qualitative inquiry through post-survey interviews was also used to strengthen the research outcomes. The findings pointed out that social media use results in greater exploitation over exploration capabilities in the study area. The possible reasons for this one-sided usage, such as lack of awareness and technical and human incapacities are explored, and a suggestion for developing ambidexterity is presented. The study’s outcome can help small business owners, employees, and the government capitalize on the different social technology tools to their most significant advantage.